The Influence of e-WOM and Korean Celebrities as Brand Ambassadors on Consumer Purchase Decision through Brand Image (Case on Somethinc Consumers in Semarang) - Komara, Nabila Rahmananda; Amie Kusumawardhani, Amie (Faculty of Economics and Business Diponegoro University, 2023)
ABSTRACT Nowadays, with the advancements in science and technology, particularly the internet, business competition has become increasingly intense, while foreign cultures, such as The Korean Wave, have become more accessible to Indonesia. Subsequently, the increased rivalry will force Somethinc, an Indonesian beauty company that is known for its wide range of skincare and beauty products, to refine their marketing strategy in order to remain competitive, enhance their brand image, and improve consumer purchase decisions, by making use of the trends of electronic word of mouth and the usage of brand ambassadors. This study aims to analyze the exact extent to which the brand ambassadors and electronic word of mouth contribute to the purchasing decisions of Somethinc customers. The population in this study are the consumers of Somethinc products in the city of Semarang, Indonesia. The sample used was 170 respondents. The sample collecting method used is purposive sampling. The data collecting method used is the distribution of questionnaires through Google Form. This study uses Structural Equation Modeling (SEM) with Partial Least Square (PLS) approach utilizing the 3th edition of SmartPLS as the analysis tool. The findings from this study illustrate that, the electronic word of mouth and brand ambassadors have a positive and significant effect on brand image. In addition, electronic word of mouth and brand ambassadors have a positive and significant effect on purchase decisions..